2015
DOI: 10.18632/oncotarget.3443
|View full text |Cite
|
Sign up to set email alerts
|

Brassinin inhibits STAT3 signaling pathway through modulation of PIAS-3 and SOCS-3 expression and sensitizes human lung cancer xenograft in nude mice to paclitaxel

Abstract: Persistent phosphorylation of signal transducers and activators of transcription 3 (STAT3) is frequently observed in tumor cells. We found that brassinin (BSN) suppressed both constitutive and IL-6-inducible STAT3 activation in lung cancer cells. Moreover, BSN induced PIAS-3 protein and mRNA, whereas the expression of SOCS-3 was reduced. Knockdown of PIAS-3 by small interfering RNA prevented inhibition of STAT3 and cytotoxicity by BSN. Overexpression of SOCS-3 in BSN-treated cells increased STAT3 phosphorylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
117
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 153 publications
(123 citation statements)
references
References 53 publications
6
117
0
Order By: Relevance
“…24,29,36 Hence, we then explored STAT3 expression in NSCLC lung tissues and their counterparts, and western-blot revealed that STAT3 protein level was increased in NSCLC lung tissues in comparison to their counterparts (3.8-fold of increase in average) ( Figure 2a , b ), which were verified by examination of STAT3 mRNA expression using qRT-PCR ( Figure 2c ). On account of the fact that STAT3 is the critical factor on controlling cell cycle, dysregulation of its protein expression might initiate and accelerate development and progression of NSCLC.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…24,29,36 Hence, we then explored STAT3 expression in NSCLC lung tissues and their counterparts, and western-blot revealed that STAT3 protein level was increased in NSCLC lung tissues in comparison to their counterparts (3.8-fold of increase in average) ( Figure 2a , b ), which were verified by examination of STAT3 mRNA expression using qRT-PCR ( Figure 2c ). On account of the fact that STAT3 is the critical factor on controlling cell cycle, dysregulation of its protein expression might initiate and accelerate development and progression of NSCLC.…”
Section: Resultsmentioning
confidence: 72%
“…34,35 STAT3 has also been revealed to benefit for tumorigenesis via accommodating cell apoptosis through facilitating Bcl-2 and Bcl-xL expression. 36 Given the pivotal role in tumor development, STAT3 represents an attractive therapeutic target for solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…STAT3 has been shown to inhibit apoptosis, the mechanism of which contributes to Lee et al 25 Thus, we analyzed the expression of STAT3, STAT3 phosphorylated tyrosine 705 (p-STAT3 (Tyr705)), two key apoptosis inhibitors Bcl-2 and Bcl-xL using western blot assays in paclitaxel-sensitive and -resistant CC cell lines. The results indicated that the expression of STAT3 and p-STAT3 (Tyr705) were increased in paclitaxel-resistant cells (HeLa/PR and CaSki/PR) when compared with paclitaxel-sensitive cells (HeLa and CaSki).…”
Section: Resultsmentioning
confidence: 99%
“…25 In this study, we determined that miR-125a can directly bind to the STAT3 3′-UTR and suppress its expression. Moreover, the expression of STAT3, Bcl-2 and Bcl-xL were significantly increased in paclitaxel-resistant CC cells.…”
Section: Discussionmentioning
confidence: 97%
“…Compounds containing this pharmacophore, therefore, can be found in varied biologically active compounds. Certain derivatives, which target allosteric modulation of cannabnoid receptor 1 (CB1), 12 glycogene phosphorylase inhibitors, 13 neurotensin (NT) (8)(9)(10)(11)(12)(13) 31 ), may act as apoptosis inducers 32 and potential DNA-intercalating compounds 33 (like duocarmycin A). In addition, they exert promising and remarkable in vitro antiproliferative effects.…”
mentioning
confidence: 99%